Pengaruh Penambahan Jenis Stabilizer terhadap Karakteristik Yoghurt Susu Kambing Etawa dengan Isolat Lactobacillus rhamnosus SKG34 - Aldianto, Muhammad Taufiq; Nocianitri, Komang Ayu; Sugitha, I Made (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 13 No 1 (2024): Jurnal ITEPADO - 10.24843/tepa.2024.v13.i01.p05, 2024)
Goat-milk yogurt problem’s is having a thin texture, especially the one using a single strain. The single strain used in this research is Lactobacillus rhamnosus SKG34. One solution to overcome this problem is by adding stabilizer. This research aims to determine the effect of adding different types of stabilizers to the characteristics of goat milk yogurt and to determine which stabilizer produces the best characteristics. This research used completely randomized design (CRD) with seven treatment levels of stabilizer addition, consisting control, 1.5% potato starch, 1.5% taro flour, 1.5% tapioca, 1% carboxymethyl cellulose, 1% pectin, and 1% whey protein concentrate. The research data analyzed by using analysis of variance (ANOVA), if the results have a significant effect, they are followed by Duncan's multiple range test (DMRT). The results show that adding different types of stabilizers has a significant effect on total lactic acid bacteria (LAB), total acidity, acidity level (pH), viscosity, hedonic (texture, taste, and overall acceptance) and scoring (texture, homogeneity, and taste) of goat milk yogurt. The addition of 1% whey protein concentrate produced the best treatment with the criteria of total LAB 3.1×107 CFU/ml, total acid 0.96%, pH value 4.81, viscosity 1708.33 cP, and sensory properties including preferred color, normal slightly goat-smell aroma, preferred slightly thick and homogeneous texture, preferred sweet and sour taste, and preferred overall acceptance. Keywords: Yogurt, Goat milk, Stabilizer, Lactobacillus rhamnosus SKG34